Management of surgical oncology patients during the COVID-19 pandemic: Short-term results - Bakir, Huseyin; Yordanagil, Mevlut; Okan, Ismail (Annals of Medical Research, 2022)
Aim: In our study, the effect of the pandemic on the treatment of surgical oncology patients and its short-term results were investigated. The Coronavirus Disease 2019 pandemic has put a heavy burden on healthcare institutions. During this period, treatment of many diseases, including cancer patients, have been disrupted. Methods: Our study was designed as a retrospective, observational study. It was investigated to what extent the treatment of patients receiving cancer treatment was affected and what changes were made in the management of patients diagnosed with cancer during the pandemic period. Results: The 148 cancer cases were discussed at Multidisciplinary Meetings (MDM) held in our clinic between December 2019 and May 2020. Of the patients, 76 (51.4%) had gastrointestinal system malignancies, 39 (26.3%) had breast malignancies, and the rest had other malignancies. There was no statistically significant difference between the mean number of cancer cases discussed in MDMs held in pre-pandemic and pandemic periods. However, it was observed that there was a statistically significant decrease in the number of operations performed during the pandemic period (p < 0.001). The treatment protocol of 14 malignancy patients was changed due to the pandemic. Of these patients, 10 were diagnosed with colorectal, 2 with gastric, 1 with breast cancer and 1 with gastrointestinal stromal tumor. Conclusion: According to the short-term results in our study, delaying surgical treatment for a while in some oncological patients and administration of systemic chemotherapy during this period when considered necessary did not have a significant negative effect on the course of the disease.